MULTIDIMENSIONAL SECURITY IN MUAY THAI PRACTICE - Neskovic, Marta (The Policy of National Security, 2026)
This article examines Muay Thai as a cultural practice that reflects the multidimensional character of human security. Once tied primarily to warfare, Muay Thai now engages multiple domains of security: physical, economic, health, and ontological. Through ethnographic accounts and historical analysis, I show how the development of Muay Thai has been shaped by the ways Thai society has understood and responded to insecurity, whether military threat, economic precarity, or existential uncertainty. Its practices provide livelihood opportunities, bodily conditioning, and ritualized forms of resilience that extend into both communal life and cosmological orientation. The analysis also considers the perspectives of foreign practitioners, revealing how national narratives meet lived realities. Ultimately, the article demonstrates that security in Muay Thai is paradoxical: the very practices that cultivate resilience and continuity simultaneously produce new vulnerabilities.
Keywords: multidimensional security; martial arts; Muay Thai; resilience and vulnerability; cultural heritage; ethnography of sport